SURVEY OF THE INFLUENCE OF SOCIAL MEDIA ACTIVISM ON STUDENTS' PERCEPTIONS REGARDING POOR HYGIENE OF PEOPLE WITH MENTAL ILLNESS IN INDONESIA: A CROSS-SECTIONAL STUDY - Lalisang, Nathania Alma Cintanya; Pratamawaty, Benazir Bona; Wibowo , Kunto Adi (Journal of Community Mental Health and Public Policy, 2024)
Background: In this digital era, there is a huge activism taking place on social media. One of the issues that is frequently discussed on social media is mental mental illness, such as anxiety and depression which are the most common disorders. People with mental illness often receive a negative stigma from society regarding their hygiene. Purpose: This research aims to see the influence of activism on students' perceptions regarding poor hygiene of people with mental illness in West Java province. Methods: This research used quantitative research methods and obtained 391 respondents through distributing questionnaires using Google Forms. Results: From 391 respondents, it was found that 75% of respondents were male and 25% were female. The results of other research also produced good validity tests (Rcount > Rtable), reliable reliability tests (Cronbach's Alpha > 0.700) but small regression tests (0.3% < 0.5%). Conclusion: Based on the research result, it can be concluded that students' perceptions of poor hygiene to people with mental illness are not only influenced by social media activism, but also by direct knowledge and experience with people mental health. Abstrak Latar Belakang: Di dunia yang serba digital ini, ada banyak aktivisme yang terjadi di sosial media. Salah satu isu yang sering dibicarakan dalam media sosial adalah mengenai mental health illness atau penyakit mental yaitu dengan penyakit seperti gangguan kecemasan dan depresi yang paling umum. Mental health illness sering mendapat stigma negatif oleh masyarakat terhadap kebersihan penderitanya. Tujuan: Penelitian ini bertujuan untuk melihat pengaruh aktivisme atas presepsi mahasiswa mengenai poor hygiene penderita mental health ilness di provinsi Jawa Barat. Metode: Penelitian ini mengacu pada metode penelitian kuantitatif dan berhasil mendapatkan 391 responden yang didapatkan melalui penyebaran kuisioner dengan Google Forms. Hasil: Dari hasil penelitian oleh 391 responden, didapatkan 75% responden yang berjenis kelamin Laki-laki dan 25% yang berjenis kelamin perempuan. Hasil penelitian lainnya juga menghasilkan uji validitas yang baik (Rhitung > Rtabel), uji realibilitas yang reliable (Cronbach’s Alpha > 0,700) namun uji regresi yang kecil (0.3% < 0,5%). Kesimpulan: Berdasarkan hasil penelitian diatas, dapat disimpulkan bahwa persepsi mahasiswa terhadap poor hygiene penderita mental health illness tidak hanya dipengaruhi oleh aktivisme media sosial, namun oleh pengetahuan dan pengalaman langsung dengan objek penderita kesehatan mental.